State-Sanctioned Hostility: The Instrumentalization of Mass Emotion Through Pakistan's Anti-Blasphemy Laws and its Impact on Christian Minorities - Fatima Raza (Muslim Politics Review, 2025)
Mass emotion plays a pivotal role in Pakistan's socio-political landscape, often acting as a catalyst for mass violence, particularly against minority communities. Negative mass emotion legitimizes sub-state violence and fosters a ‘herd mentality’, which perpetuates an 'us versus them' paradigm. This dynamic has had dire consequences for Pakistan's Christian minority, who have repeatedly been the targets of state-sanctioned hostility. This paper explores the origins of mass emotion that incites violence against minorities, especially Christians, within the context of Pakistan's anti-blasphemy laws. It illuminates how mass emotion incites violence against minorities, particularly Christians, in the context of Pakistan's anti-blasphemy laws. The case of Asia Bibi serves as an example of how these laws, manipulated by the state, can arouse mass emotion and incite violence. Furthermore, this paper examines how the Pakistan Supreme Court's discourse during Asia Bibi’s trial attempted to mitigate mass emotion by invoking ethical principles derived from the Prophet Muhammad's teachings on the treatment of Christians.